Deterrence in the 21st Century Statecraft in the Information Age - Ouellet, Eric; D'Agata, Madeleine; Stewart, Keith (Beyond Boundaries, 2024)
The information age has opened a new front of adversarial statecraft. The past decades have seen the rise and refinement of conflict enacted in the world of information, with tactics including seeding disinformation, the theft of sensitive data, confusing or obscuring public opinion to forward specific goals, and beyond. Deterrence in the 21st Century asks how, and if it is indeed possible, to deter an enemy in the realm of information warfare. Setting the stage with an overview of key concepts of deterrence in the information age, the book presents new conceptual approaches and their possible applications. Bringing together some of the most respected analysts working today, Deterrence in the 21st Century looks beyond the technical aspects of the use of information and disinformation as adversarial statecraft to seek new avenues to deter the undermining of institutions and societies. Treating deterrence as a concept, a policy, a social challenge, and a series of practical solutions, Deterrence in the 21st Century presents theoretical approaches, conceptual analysis, empirical research, and content analysis. This is a thorough, thoughtful, and expert analysis of one of the most difficult and essential security challenges of our time. With contributions by: Christopher Ankersen, Yair Ansbacher, Oshri Bar-Gill, Stephen J. Cimbala, Maddie D'Agata, Molly Ellenberg, Leandre R. Fabrigar, Rachel Lea Heide, Nicole J. Jackson, Pierre Jolicoeur, Christian Leuprecht, Adam Lowther, Sarah Jane Meharg, Eric Ouellet, Ronald D. Porter, Anthony Seaboyer, Ron Schleifer, Miniqian Shen, Anne Speckhard, Keith Stewart, Joseph Szeman, and Alex Wilner